2024
DOI: 10.3390/su16041439
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cultural Sustainability: Making Rescue Excavations Accessible through Educational Applications and Virtual Reality

Stavros Vlizos,
Konstantinos Kotsopoulos,
Dimitrios Christodoulou

Abstract: The key questions of this article concern the extent to which digital documentation, 3D scanning technologies, and VR/AR technologies contribute to the preservation, enhancement, and sustainability of cultural heritage. The purpose of this research is to present an innovative methodology through which a platform for the diagnosis, management, and documentation of findings, progress, and reports and projections of rescue excavations in the area of Euboea, Greece was implemented. A holistic approach is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Kihong Kim et al [36] demonstrated that the VR-enhanced environment brings novel museum experiences, resulting in greater impact and enjoyment for visitors in terms of learning. There are numerous similar studies on VR cultural heritage [37][38][39][40][41].…”
Section: Cultural Heritage Visual Presentationmentioning
confidence: 99%
“…Kihong Kim et al [36] demonstrated that the VR-enhanced environment brings novel museum experiences, resulting in greater impact and enjoyment for visitors in terms of learning. There are numerous similar studies on VR cultural heritage [37][38][39][40][41].…”
Section: Cultural Heritage Visual Presentationmentioning
confidence: 99%